2020
DOI: 10.1177/1745691620942516
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Vulnerabilities to Upper Respiratory Infectious Illness: Implications for Susceptibility to Coronavirus Disease 2019 (COVID-19)

Abstract: For 35 years, our laboratory has been involved in identifying psychosocial factors that predict who becomes ill when they are exposed to a virus affecting the upper respiratory tract. To pursue this question, we used a unique viral-challenge design in which we assessed behavioral, social, and psychological factors in healthy adults. We subsequently exposed these adults to a cold or influenza virus and then monitored them in quarantine for 5 to 6 days for onset of respiratory illness. Factors we found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 71 publications
1
87
0
2
Order By: Relevance
“…Several experimental studies suggest a dose-dependent association between psychological stress and acute infectious respiratory illness. 4 , 21 , 22 Similarly, studies using large population-based registers 5 , 23 have shown an association between psychiatric disorders, especially stress-related disorder, and subsequent severe infections in the general population. Recent studies have examined these associations in the context of the COVID-19 pandemic, indicating that a range of psychosocial factors, 11 including self-reported symptoms of psychological distress, and certain psychiatric disorders (depression, 12 substance use, and schizophrenia 13 ) were associated with an increased risk of COVID-19.…”
Section: Discussionmentioning
confidence: 98%
“…Several experimental studies suggest a dose-dependent association between psychological stress and acute infectious respiratory illness. 4 , 21 , 22 Similarly, studies using large population-based registers 5 , 23 have shown an association between psychiatric disorders, especially stress-related disorder, and subsequent severe infections in the general population. Recent studies have examined these associations in the context of the COVID-19 pandemic, indicating that a range of psychosocial factors, 11 including self-reported symptoms of psychological distress, and certain psychiatric disorders (depression, 12 substance use, and schizophrenia 13 ) were associated with an increased risk of COVID-19.…”
Section: Discussionmentioning
confidence: 98%
“…Further study of factors that promote resilience in the context of COVID-19 pregnancies could also lead to the development of interventions. Additionally, the influence of stress on infection and inflammatory processes highlights a need to investigate the interaction of pandemic-related perinatal stress with COVID-19 infection ( Acabchuk et al, 2017 ; Cohen, 2020 ; Simons et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Authors of one review analyzed several studies related to lockdown periods following upper respiratory tract viruses [ 52 ] and found several factors associated with health risks such as smoking, diet, and psychological stress. In contrast with these, PA, social integration and support, good sleep quality, and mild alcohol intake seemed to reduce health risks.…”
Section: Discussionmentioning
confidence: 99%